THE EFFECT OF ORGANIZATIONAL CULTURE, ENTREPRENEURIAL PERSONALITY, AND TRUST ON THE MANAGERIAL EFFECTIVENESS OF BRANCH MANAGERS OF THE PRACTICAL EDUCATION CENTER - YUSTANTINA, EKA YUNITA (PPs UNJ, 2016)
This research aims to examine the hypothesis whether managerial effectiveness is affected by organizational culture, entrepreneurial personality, and trust pertaining in an organization. This study used survey method with four questionnaires to collect the data and Path statistical technique to analyze them. This causal study involved 80 Branch Managers of the Practical Education Center as the sample. They were randomly selected from the overall population of 207 branches in the areas of Jakarta, Depok, Tangerang and Bekasi. The result revealed that there was positive direct effects of (1) the organizational culture toward the managerial effectiveness; (2) the entrepreneurial personality toward the managerial effectiveness; (3) the level of trust toward the managerial effectiveness; (4) the organizational culture toward the level of trust; (5) the entrepreneurial personality toward the level of trust. It implies that the managerial effectiveness of the branch managers can be improved by enhancing the implementation of organizational culture, developing the entrepreneurial personality and improving the level of trust in the company.